Pemanfaatan Progress Test sebagai Tolak Ukur Keberhasilan Belajar Mengajar - Mirfat Mirfat; Yuhernita Yuhernita (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2014)
Background: Faculty of Medicine, YARSI University has experienced a paradigm shift in higher education from a content-based curriculum to a competency-based curriculum that has been applied since the academic year of 2007/2008 using a problem-based learning approach. Progress test is an evaluation that is used to measure the student’s competency in the field of knowledge in its entirety. Faculty of Medicine, YARSI University has yet to apply these progress test. Thus, this research is aimed to execute a progress test trial in attempt to use it as a standard measurement to observe student capabilities in the field of knowledge, either as the individual or as a whole class.Method: This research uses a qualitative method. The research sample consists of 200 students from the faculty of medicine chosen by using a randomized approach for each class, starting from the class of 2013 (first year students) until the class of 2010 (fourth year students).Results: Based on student entrance levels in years, 4th year students had acquired a higher score on the progress test trial in comparison to the 1st, 2nd and 3rd year students. The results had also shown that the students in their first year of study had lower scores when compared to the students in their last year of study (4th year). This indicates that the longer the period of study or the more time spent in the study process, the better the scores achieved on the progress test.Conclusion : Faculty of Medicine, YARSI University has successfully executed the progress test trial in the first week of the third block in the odd semester of the academic year of 2013/2014. The progress test itself consisted of 200 questions and was taken by 200 student samples that were chosen in a randomized manner. The results of the progress test had revealed that there was an increase in the average examination grades of students in the 1st year until the 4th year, which is consistent with the level of understanding of lectures accordingly to each year. Item Analysis on the test showed a good distribution in the level of difficulty, where the majority of questions were held in the moderate level of difficulty.